Supramolecular co-assembly of water-soluble nucleobase-containing copolymers: bioinspired synthetic platforms towards new biomimetic materials. Issue 39 (14th September 2022) - Arsenie, Laura Vasilica; Semsarilar, Mona; Brendel, Johannes C.; Lacroix-Desmazes, Patrick; Ladmiral, Vincent; Catrouillet, Sylvain
Abstract : This study presents the development of co-assembled copolymer architectures at physiological pH (pH 7.4) formed via H-bonds between complementary nucleobase-containing copolymers. Abstract : This study presents the development of co-assembled copolymer architectures at physiological pH (pH 7.4) formed via H-bonds between complementary nucleobase-containing copolymers. Well-defined hydrophilic copolymers were synthesised by RAFT polymerisation: statistical uracil- and thiomorpholine oxide-containing copolymers P(UrMA n - stat -THOXMA m ) as well as diblock copolymers PEG112 - b -P(AdMA n - stat -THOXMA m ) composed of a PEG block and a second block of a copolymer of adenine- and thiomorpholine oxide-derived methacrylates. Binary mixtures of the resulting copolymers formed co-assembled nanoobjects in aqueous solution as a result of the H-bonds established between nucleobases. The influences of the polymer architecture (degree of polymerisation, co-monomer composition, length of the nucleobase-containing block), the ratio between complementary nucleobases, and the impact of H-bond competitors on the self-assembly properties were investigated. Light scattering techniques (SLS, DLS) and transmission electron microscopy (TEM) were used to characterise the co-assembled objects. This study demonstrates that the size of the resulting co-assemblies was mainly governed by the type and content of nucleobases, and by the length of the nucleobase block. Moreover, the in vitro evaluation of the nucleobase-containing polymers revealed that they were non-cytotoxic and hemocompatible. This study increases the understanding of nucleobase pairing in artificial copolymer architectures which are potential platforms for further use in biosciences.